Research on modeling and simulation of traction power supply system of guideway rubber-tires train - Haida Xu; Liwei Zhang; Jiapeng Wang; Xu Wang (International Journal of Electrical Power & Energy Systems)
Guideway rubber-tires system, also known as Rapid rubber-tires trail (RRT), is a new type of urban rail transit. The train uses rubber tires as running wheels and uses guide rails to achieve steering. The guideway rubber-tires train generally adopts the power supply mode of on-board energy storage and can operate in an unmanned way. Through the simulation research of traction power supply system of guideway rubber-tires train, it can provide important support data for system planning and design, economic benefit evaluation and safety performance monitoring. In this paper, the component model of traction power supply system of guideway rubber-tires train is established. According to the dynamic multi-train condition, the execution flow of AC-DC power flow calculation is proposed, the load simulation of traction power supply system is realized, and the calculation results are analyzed. On the basis of normal condition simulation, fault condition simulation is carried out. The simulation results mainly include the performance of key components in the traction power supply system, the simulation of the fault charging curve of the vehicle overcapacity, and the verification of the redundancy performance of the line. The results show that the simulation system can simulate the normal and fault conditions of the traction power supply system well, and the simulation results show that the traction power supply system of the line meets the design requirements.